HELIOS-expressing human CD8 T cells exhibit limited effector functions - Neyens, Damien; Hirsch, Thibault; Abdel Aziz Issa Abdel Hadi, Achraqat; Dauguet, Nicolas; Vanhaver, Christophe; Bayard, Alexandre; Wildmann, Claude; Luyckx, Mathieu; Squifflet, Jean-Luc; D’Hondt, Quentin; Duhamel, Céline; Huaux, Antoine; et al. (Frontiers in Immunology, 2023)
Abstract The transcription factor HELIOS is primarily known for its expression in CD4 regulatory T cells, both in humans and mice. In mice, HELIOS is found in exhausted CD8 T cells. However, information on human HELIOS+ CD8 T cells is limited and conflicting. In this study, we characterized by flow cytometry and transcriptomic analyses human HELIOS+ CD8 T cells, which primarily consist of memory cells and constitute approximately 21% of blood CD8 T cells. In comparison with memory HELIOS- T-BEThigh CD8 T cells that displayed robust effector functions, the memory HELIOS+ T-BEThigh CD8 T cells produce lower amounts of IFN- and TNF- and have a lower cytotoxic potential. We wondered if these cells participate in the immune response against viral antigens, but did not find HELIOS+ cells among CD8 T cells recognizing CMV peptides presented by HLA-A2 and HLA-B7. However, we found HELIOS+ CD8 T cells that recognize a CMV peptide presented by MHC class Ib molecule HLA-E. Additionally, a portion of HELIOS+ CD8 T cells is characterized by the expression of CD161, often used as a surface marker for identifying TC17 cells. These CD8 T cells express TH17/TC17-related genes encoding RORt, ROR, PLZF, and CCL20. Our findings emphasize that HELIOS is expressed across various CD8 T cell populations, highlighting its significance beyond its role as a transcription factor for Treg or exhausted murine CD8 T cells. The significance of the connection between HELIOS and HLA-E restriction is yet to be understood.